Effects of Rural Non-Farm Employment on Poverty and Income Distribution: Evidence for Macedonia and Slovenia - Moellers, Judith (Journal of Income Distribution®, 2011)
Most of the poor in Eastern Europe belong to families with at least one working member, meaning that work per se does not protect families from poverty. As farm families in particular are characterized by an elevated poverty risk, rural non-farm employment (RNFE) could, however, curtail increases in economic vulnerability and inequality. This article analyzes the effect of RNFE on poverty reduction and inter-household income distribution in rural Macedonia and Slovenia. The research is based on an empirical household survey. Results show a high dependency on non-farm incomes; smaller farms particularly benefit from RNFE. The analysis of decomposed Gini coefficients reveals a smoothing effect of non-farm employment on income distribution.